Explaining the Factors Affecting the Distribution of Land Use Change Interests Using the Communicative Planning Framework - Mohsen Abdehkolahchi; Abdehkolahchi Ghalehnoee (تحقیقات کاربردی علوم جغرافیایی)
Urban land use change is one of the key issues in urban planning that has been addressed by researchers in many different aspects, especially from the perspective of space. But the point that has been overlooked in various studies is that the analysis of different aspects of land use change is not limited to classical and spatial factors, and because of the various interest of land use change, many stakeholders aim to derive interest from this process in urban land developments. Accordingly, this paper aims to apply the communicative planning framework in identifying and explaining the factors affecting the distribution of land use change interests, because communicative planning as one of the major urban planning theories has focused on proper distribution of interests among stakeholders. In this study, after formulating the study results from theoretical studies, using a quantitative approach and exploratory factor analysis technique, the factors affecting the distribution of land use change interests have been identified and explained based on Approvals of the Commission Article 5 of the Ahvaz City (as one of the official references to land use change in the urban planning system). The results show that 9 factors with cumulative variance of 70/851% provide a proper explanation of user change interests distribution, among which "mediation legitimacy of planners and decision makers" has the most effect. Of course, the quality of these factors with 42.31% of the land quality shows the distribution of land use interests among the stakeholders was not very appropriate, which can lead to interest conflicts, especially between groups with economical-political interests and the public interest, and thus cause social instability in Ahvaz city.